2019
DOI: 10.4055/cios.2019.11.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play after Modified Broström Operation for Chronic Ankle Instability in Elite Athletes

Abstract: Background This study assessed the average time to return to training and official game participation after modified Broström operation (MBO) in elite athletes. Methods Sixty athletes diagnosed with lateral ankle instability underwent MBO from October 2011 to December 2013. Their average age was 19.3 years, and the average follow-up time was 28.8 months. We measured the time sequence of three phases of rehabilitation: start of personal training, start of team training, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 20 publications
0
46
0
4
Order By: Relevance
“…Until now, no validated questionnaire specific to the evaluation of clinical outcomes of treatment for Achilles tendon rupture, such as the VISA-V [ 29 ] or Leppilahti score [ 30 ], has been validated in Korean. Therefore, we used the FAOS to evaluate the validity of the Korean translation of the ATRS because the FAOS has been validated in Korean and has been used to assess the outcomes of Achilles tendon rupture, as well as the validity of other translations of the ATRS [ 5 , 6 , 11 , 12 , 18 , 31 ]. In previous validation studies, the correlation with the FAOS ranged from 0.6 to 0.84 in a Swedish [ 5 ], 0.72 to 0.87 in Dutch [ 12 ], 0.61 to 0.8 in Norwegian [ 6 ], and 0.55 to 0.83 in Persian populations [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, no validated questionnaire specific to the evaluation of clinical outcomes of treatment for Achilles tendon rupture, such as the VISA-V [ 29 ] or Leppilahti score [ 30 ], has been validated in Korean. Therefore, we used the FAOS to evaluate the validity of the Korean translation of the ATRS because the FAOS has been validated in Korean and has been used to assess the outcomes of Achilles tendon rupture, as well as the validity of other translations of the ATRS [ 5 , 6 , 11 , 12 , 18 , 31 ]. In previous validation studies, the correlation with the FAOS ranged from 0.6 to 0.84 in a Swedish [ 5 ], 0.72 to 0.87 in Dutch [ 12 ], 0.61 to 0.8 in Norwegian [ 6 ], and 0.55 to 0.83 in Persian populations [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the residual ATFL ligament in CLAI is still of good quality, and the position of the ligament is superficial, the Broström procedure and modified Broström procedure for suturing extensor retinaculum have become the standard procedures for treatment of CLAI since Broström reported successful treatment of CLAI in 1996 by the direct repair of ATFL. Although the previous reports indicated that use of the Broström procedure of direct repair of ATFL for CLAI has achieved satisfactory clinical results, there was still a 6% to 25% complication rate including ankle pain, ankle swelling, and recurrence of lateral ankle instability. With the development of orthopaedic endoscopy, some clinicians adopted arthroscopy‐assisted ATFL repair, first using arthroscopy to deal with ankle and surrounding lesions, and then performing open suture repair for ATFL.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, no validated questionnaire speci c to the evaluation of clinical outcomes of treatment for Achilles tendon rupture, such as the VISA-V [27] or Leppilahti score [28], has been validated in Korean. Therefore, we used the FAOS to evaluate the validity of the Korean translation of the ATRS because the FAOS has been validated in Korean and has been used to assess the outcomes of Achilles tendon rupture, as well as the validity of other translations of the ATRS [4,5,11,17,29]. The overall correlation between the Korean translation of the ATRS and the FAOS was above 0.7.…”
Section: Discussionmentioning
confidence: 99%